Genome Sequence of vB_AbaS_TRS1, a Viable Prophage Isolated from Acinetobacter baumannii Strain A118 - Turner, Dann (Genome Announc, 2016)
A novel temperate phage, vB_AbaS_TRS1, was isolated from cultures of Acinetobacter baumannii strain A118 that had been exposed to mitomycin C. Phage TRS1 belongs to the Siphoviridae family of bacteriophages and encapsulates a 40,749-bp genome encoding 70 coding sequences and a single tRNA.